Ultrastructural Changes in the White and Gray Matter of Mice at Chronic Time Points After Repeated Concussive Head Injury. Issue 10 (October 2015) - Ojo, Joseph O.; Bachmeier, Corbin; Mouzon, Benoit C.; Tzekov, Radouil; Mullan, Michael; Davies, Heather; Stewart, Michael G.; Crawford, Fiona
<x xml:space="preserve">Abstract</x> Abstract Mild traumatic brain injury is a risk factor for neurodegenerative disease. We recently developed a model of repetitive concussive injury in mice that we have extensively characterized from 24 hours to 24 months after injury. Animals show evidence of progressive spatial memory deficits, thinning of the corpus callosum, axonal injury, and neuroglial activation. Here, we extended our neuropathologic characterization to the ultrastructural level in both a qualitative and a quantitative study. We focused on chronic (3 and 6 months) postinjury time points when the earliest stages of degenerative secondary changes were previously observed. In both C57BL/6 and hTau mice, we found white matter damage typified by axonal degeneration, microglial phagocytosis, and increased neuroglial cell density. In the cerebral cortex, we observed evidence of synaptic degeneration, dark neurons, altered dendritic microfilaments, subtle changes to the microvasculature, a mild augmentation of age-related features such as lipofuscin deposition, and electron-dense inclusions in microglial and perivascular cells. The majority of these ultrastructural features seemed to be more prominent at 3 versus 6 months after injury. Similar patterns were observed in C57BL/6 and hTau mice. These findings further support the relevance of our concussive injury model to the consequences of repetitive mild traumatic brain injury in humans.